Incidence and Characterization of Integrons, Genetic Elements Mediating Multiple-Drug Resistance, in Avian Escherichia coli - Bass, Lydia (American Society for Microbiology, 1999)
Antibiotic resistance among avian bacterial isolates is common and is of great concern to the poultry industry. Approximately 36% (n = 100) of avian, pathogenic Escherichia coli isolates obtained from diseased poultry exhibited multiple-antibiotic resistance to tetracycline, oxytetracycline, streptomycin, sulfonamides, and gentamicin. Clinical avian E. coli isolates were further screened for the presence of markers for class 1 integrons, the integron recombinase intI1 and the quaternary ammonium resistance gene qacEΔ1, in order to determine the contribution of integrons to the observed multiple-antibiotic resistance phenotypes. Sixty-three percent of the clinical isolates were positive for the class 1 integron markers intI1 and qacEΔ1. PCR analysis with the conserved class 1 integron primers yielded amplicons of approximately 1 kb from E. coli isolates positive for intI1 and qacEΔ1. These PCR amplicons contained the spectinomycin-streptomycin resistance gene aadA1. Further characterization of the identified integrons revealed that many were part of the transposon Tn21, a genetic element that encodes both antibiotic resistance and heavy-metal resistance to mercuric compounds. Fifty percent of the clinical isolates positive for the integron marker gene intI1 as well as for the qacEΔ1 and aadA1 cassettes also contained the mercury reductase gene merA. The correlation between the presence of the merA gene with that of the integrase and antibiotic resistance genes suggests that these integrons are located in Tn21. The presence of these elements among avian E. coli isolates of diverse genetic makeup as well as in Salmonella suggests the mobility of Tn21 among pathogens in humans as well as poultry.